Customer behaviour in restaurant establishments in South Africa during the COVID-19 pandemic - Deen, Anisah; Kuhudzai, Anesu Gelfand; Geyser, Ita (Journal of Applied Sciences in Travel and Hospitality, 2025)
The tourism and hospitality industry was adversely impacted by the COVID-19 pandemic. Restaurants were affected greatly as businesses shut down because of the lockdown restrictions and limited movement within the country. There were distinct customer behavioural differences when visiting and dining in restaurants. These establishments were expected to execute the recommended safety protocols. Due to the lack of South African studies of this nature, this paper explores the shifts in customer behaviour when customers paid visits to various restaurant establishments in the Gauteng province of South Africa. Using the convenience sampling technique, the study achieved a valid sample size of 156 respondents by visiting ten restaurants. A quantitative research method was applied for an existing questionnaire that included Likert scale questions as well as open ended questions. The data was analysed using an exploratory factor analysis (EFA) as well as a dimension reduction technique. Findings indicate that customers’ behaviour has radically changed when dining out as a direct result of COVID-19. Quantitative analysis illustrates three factors: delivery service option, hospitality establishment hygiene and cleanliness and safety measures are viewed as the distinctive behaviours that customers were gravitating toward as lockdown restrictions eased.  Open-ended responses were analysed using content analysis whereby three themes emerged, namely: feelings of being unsafe; fear of contracting the virus and willingness to return to restaurants. Aspects such as cleanliness, physical environment and availability of delivery services are significant when it comes to customers’ willingness to dine in hospitality establishments during the COVID-19 pandemic.